1996
DOI: 10.1111/j.1945-5100.1996.tb02022.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure history of the Torino meteorite

Abstract: Abstract— We determined He, Ne, Ar, 10Be, 26Al, 36Cl, and 14C concentrations, as well as cosmic‐ray track densities and halogen concentrations in different specimens of the H6 chondrite Torino, in order to constrain its exposure history to cosmic radiation. The Torino meteoroid had a radius of ∼20 cm and travelled in interplanetary space for 2.5–10 Ma. Earlier, Torino was part of a larger body. The smallest possible precursor had a radius of 55 cm and a journey through space longer than ∼65 Ma. If the first‐st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 31 publications
(21 reference statements)
2
47
0
Order By: Relevance
“…The solar noble gases may suggest that at least some grains were indeed exposed in space as IDPs. In the second approach, we estimate that at least 42% of the sample material is extraterrestrial, by simply comparing the measured amount of 14 C with an expected upper limit of 30 dpm/kg for a meteoroid with a radius of 10 cm (Wieler et al 1996). Lower 14 C production rate estimates would give larger extraterrestrial fractions.…”
Section: Some Boundary Conditions For Spwwmentioning
confidence: 99%
“…The solar noble gases may suggest that at least some grains were indeed exposed in space as IDPs. In the second approach, we estimate that at least 42% of the sample material is extraterrestrial, by simply comparing the measured amount of 14 C with an expected upper limit of 30 dpm/kg for a meteoroid with a radius of 10 cm (Wieler et al 1996). Lower 14 C production rate estimates would give larger extraterrestrial fractions.…”
Section: Some Boundary Conditions For Spwwmentioning
confidence: 99%
“…There is also a possibility of implanted of higher-energy (up to 10's of MeV) particles emitted during solar flares (e.g. Wieler et al 1996;Nishiizumi et al 1997). As already mentioned, Begemann et al (1972) first suggested that the very surface layer of lunar samples could be implanted with solar 14 C. Fireman et al (1976Fireman et al ( , 1977 found higher than expected levels of 14 C in the 600-1000 °C temperature fractions of the Apollo 11 soil 10084 and Apollo 17 trench soils 73221, 73241 and 73261, which they interpreted as implanted solar wind 14 C. If implanted from the solar wind and not another source, this result would imply a 14 C/ 1 H ratio in the solar wind of ~5 × 10 −11 .…”
Section: Implanted Energetic Particlesmentioning
confidence: 99%
“…Fluxes for SCR are quoted for proton energies >10 MeV and for a 4π solid angle, defined as J 10 , and has units of protons/cm 2 /s. Values of R 0 in the range 70 to 125 MV have been fitted to a variety of radionuclide data from Figure 1 Depth dependence of GCR production of 14 C in meteoroids of different radii (from Wieler et al 1996). The horizontal line is the mean value observed for H6 falls, with the dashed lines showing the range observed.…”
Section: Radiocarbon In Lunar Samplesmentioning
confidence: 99%
See 2 more Smart Citations